2009
DOI: 10.1016/j.jbiotec.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The use of redox potential to monitor biochemical HCBD dechlorination

Abstract: The microbial reductive dechlorination of chlorinated solvents is a redox reaction in which the chlorinated carbon receives electrons from a suitable electron donor. Hexachloro-1,3-butadiene (HCBD) is a particularly recalcitrant chlorinated solvent. Its slow, cyanocobalamin-dependent biochemical dechlorination by mixed microbial consortia had been previously demonstrated. This study shows that the reductive dechlorination reaction of HCBD can be monitored in situ by recording the redox potential (E Ag/AgCl ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[34][35][36] The dechlorination products of HCBD were also detected in both environmental media and laboratory experiments. 37,38 Therefore, the most possible dechlorination products, including penta-chlorobutadiene, tetrachlorobutadiene and tri-chlorobutadiene, were analyzed in the pumpkin samples herein. Because no commercial standards were available, characteristic ions for qualitative analysis of these metabolites were chosen according to former studies.…”
Section: Mass Balance and Possible Metabolismmentioning
confidence: 99%
“…[34][35][36] The dechlorination products of HCBD were also detected in both environmental media and laboratory experiments. 37,38 Therefore, the most possible dechlorination products, including penta-chlorobutadiene, tetrachlorobutadiene and tri-chlorobutadiene, were analyzed in the pumpkin samples herein. Because no commercial standards were available, characteristic ions for qualitative analysis of these metabolites were chosen according to former studies.…”
Section: Mass Balance and Possible Metabolismmentioning
confidence: 99%
“…Redox potential provides insights into thermodynamic feasibility, electron donor availability, and the environmental conditions that influence chemical reactions. A continuous redox potential drop is observed during dechlorination reaction . Dolfing et al first confirmed that calculated redox potentials are accurate enough to correctly predict anaerobic degradation pathways of hexachlorobenzene, but further application to a complex dechlorination scenario has never been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…A continuous redox potential drop is observed during dechlorination reaction. 45 Dolfing et al 46 first confirmed that calculated redox potentials are accurate enough to correctly predict anaerobic degradation pathways of hexachlorobenzene, but further application to a complex dechlorination scenario has never been achieved. In the present study, PCB dechlorination is transformed into a stepwise reaction sequence, and the redox potential is utilized as the indicator to predict PCB dechlorination pathways and fluxes.…”
Section: ■ Introductionmentioning
confidence: 99%